Positive electrode active material, method for manufacturing the same, positive electrode sheet, battery, and electric device
Patent Information
- Application Number
- CN202511434666.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-30
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-09-30
AI Technical Summary
然而,O3型层状氧化物正极活性材料仍然面临着以下几个关键问题:动力学性能不理想,O3型层状氧化物正极活性材料的层状结构中,由于Na离子半径大,而钠层中两相邻八面体间的四面体间隙较窄,致使O3型层状氧化物正极活性材料表现出高钠离子迁移势垒,钠离子扩散动力学性能以及倍率性能不够理想;高电压循环性能差,O3型层状氧化物正极活性材料在高电压下(≥4.0V,VS Na+/Na)易出现过渡金属层滑移动、金属离子迁移,阴离子氧化还原等现象,导致不可逆相变、晶体被结构破坏、容量快速衰减等问题;O3型层状氧化物正极活性材料与电解液间副反应,高电压下电解液易与正极发生一系列副反应,造成活性物质损失,循环产气增加等问题
Smart Images

Figure CN121282158B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of batteries, specifically to positive electrode active materials and their preparation methods, positive electrode sheets, batteries, and electrical devices. Background Technology
[0002] Sodium resources have advantages over lithium resources, such as higher abundance, lower cost, and easier processing and extraction. In recent years, sodium-ion batteries have been considered the most promising complement to lithium-ion batteries. The positive electrode active material, as the core of a sodium-ion battery, determines the overall energy and power density of the cell.
[0003] Sodium-ion battery cathode active materials mainly include layered oxide type cathode active materials, Prussian blue type cathode active materials, and polyanionic type cathode active materials. Among them, layered oxide type cathode active materials have received widespread attention from researchers and new energy companies due to their advantages such as high capacity and ease of industrialization.
[0004] In layered oxide cathode active materials, the Na content of O3-type layered oxide cathode active materials is often higher than that of P2-type layered oxide cathode active materials, thus typically exhibiting a higher specific capacity. However, O3-type layered oxide cathode active materials still face several key challenges: unsatisfactory kinetic performance; due to the large radius of Na ions and the narrow tetrahedral gaps between adjacent octahedra in the sodium layer, O3-type layered oxide cathode active materials exhibit a high sodium ion migration barrier, resulting in less than ideal sodium ion diffusion kinetics and rate performance; poor high-voltage cycling performance; O3-type layered oxide cathode active materials exhibit poor high-voltage cycling performance (≥4.0V, VS Na...). + / Na) is prone to phenomena such as transition metal layer slip, metal ion migration, and anion redox, leading to problems such as irreversible phase transition, crystal structure destruction, and rapid capacity decay; side reactions between O3-type layered oxide positive electrode active material and electrolyte, and a series of side reactions between electrolyte and positive electrode under high voltage, resulting in loss of active material and increased gas production in circulation. Summary of the Invention
[0005] This application aims to at least partially solve one of the technical problems in related technologies. This application proposes a positive electrode active material and its preparation method, a positive electrode sheet, a battery, and an electrical device. The positive electrode active material proposed in this application has high stability and can improve the rate performance and cycle performance of the battery.
[0006] A first aspect of this application provides a positive electrode active material, the positive electrode active material comprising an O3-type layered oxide, the positive electrode active material comprising a compound represented by Formula I: Na x (Nia Fe b Mn c T n M p )F k O q Formula I, wherein 0.80≤x≤1.10, 0.30≤a≤0.35, 0.30≤b≤0.35, 0.30≤c≤0.35, 0<n≤0.5, 0<p≤0.05, a+b+c+n+p=1, 0.01≤k≤0.1, k+q=2, T comprises one or more of Cu, Co, V, Mg, Ca, Sn, Zn, Cr, Ti, Al, Zr, Nb, Y, W, La, and Li, and M comprises one or more of Zn, Al, Ti, Li, Cu, Co, B, V, Cr, Ca, Mg, Sn, Zr, Nb, Y, W, and La; the sodium layer spacing of the positive electrode active material is dNa, the transition metal layer spacing thereof is dTMO2, 3.6500Å<dNa<3.6600Å, and 1.7200Å<dTMO2<1.7225Å.
[0007] The positive electrode active material proposed in the present application is an O3-type layered oxide, which can improve the capacity of the battery. By controlling the sodium layer spacing and the transition metal layer spacing of the positive electrode active material, the sodium layer spacing is relatively large and expanded, and the transition metal layer spacing is relatively small and shrunk, which can ensure an ideal sodium ion diffusion rate of the positive electrode active material, while inhibiting the slip of the transition metal layer during charge and discharge, and improving the capacity, rate performance and cycle stability of the battery.
[0008] According to some embodiments of the present application, in the XRD pattern of the positive electrode active material, a characteristic diffraction peak of the (104) crystal plane is present at 2θ of 40°-42.5°, and the full width at half maximum of the characteristic diffraction peak of the (104) crystal plane is W 104 , 0.179°≤W 104 ≤0.202°.
[0009] According to some embodiments of the present application, the XRD pattern of the positive electrode active material has a characteristic diffraction peak of the (003) crystal plane, and the 2θ of the characteristic diffraction peak of the (003) crystal plane is B 003 , 16.580°≤B 003 ≤16.630°.
[0010] According to some embodiments of the present application, the unit cell parameters a and c of the positive electrode active material satisfy: 2.9664Å<a<2.9810Å 16.1200Å<c<16.1450Å.
[0011] According to some embodiments of this application, 5.4250 <c / a<5.4420。
[0012] According to some embodiments of this application, the positive electrode active material layer includes a body and a coating layer formed on at least a portion of the surface of the body, the coating layer including a metal fluoride.
[0013] According to some embodiments of this application, based on the total mass of the positive electrode active material, the mass percentage of element M is ω(M), where 0.1% < ω(M) < 2%.
[0014] According to some embodiments of this application, based on the total mass of the positive electrode active material, the mass percentage of fluorine is ω(F), where 0.15×ω(M)<ω(F)<0.70×ω(M).
[0015] A second aspect of this application provides a method for preparing the positive electrode active material provided in the first aspect of this application, the method comprising: The positive electrode active material precursor, sodium source, and optionally T source are mixed and sintered once to obtain positive electrode active material A. The positive electrode active material A is crushed, mixed with source M, placed in a low-temperature plasma device, and a fluorine-containing gas is introduced to carry out a low-temperature plasma reaction to obtain the modified positive electrode active material. The modified positive electrode active material is subjected to secondary sintering to obtain the positive electrode active material.
[0016] In the preparation of the positive electrode active material, this application utilizes a low-temperature plasma reaction to perform low-temperature plasma-assisted mixing of the positive electrode active material and the M source under a fluorine-containing gas atmosphere, thereby exciting the fluorine-containing gas to generate highly active fluorine-containing free radicals (F, F). - CF3 + CF2 2+ CF3 - (etc.), and interact with the M source to form a sodium-loving metal fluoride modified layer on the surface of the positive electrode active material particles, effectively improving the uniformity of the surface fluorine modified layer, and allowing some fluorine elements to enter the lattice of the positive electrode active material. This results in a larger sodium layer spacing, which is expanded, and a smaller transition metal layer spacing, which is contracted. This ensures the ideal sodium ion diffusion rate of the positive electrode active material, while suppressing the slippage of the transition metal layer during charging and discharging, thereby improving the battery's capacity, rate performance, and cycle stability.
[0017] According to some embodiments of this application, the voltage of the low-temperature plasma reaction is 5kV-20kV.
[0018] According to some embodiments of this application, the frequency of the low-temperature plasma reaction is 30kHz-70kHz.
[0019] According to some embodiments of this application, the flow rate of the fluorine-containing gas is 3 slm-20 slm.
[0020] According to some embodiments of this application, the fluorinated gas comprises a mixture of an inert gas and a fluorinated organic gas, wherein the volume ratio of the inert gas to the fluorinated organic gas is 2.5:7.5-8:2.
[0021] According to some embodiments of this application, the inert gas includes one or more of helium, argon, and nitrogen.
[0022] According to some embodiments of this application, the fluorinated organic gas includes one or more of CF4, C4F8, C5F8, and C6F6.
[0023] According to some embodiments of this application, after the positive electrode active material A is crushed, the particle size corresponding to 50% of the particle size volume distribution is D. 50 The particle size corresponding to 90% of the volume distribution is D. 90 The particle size corresponding to a volume distribution of 10% is D. 10 K 90 =(D 90 -D 10 ) / D 50 ;D 50 The micrometer size is 1.5 μm-8.0 μm, preferably 2.0 μm-6.5 μm, more preferably 4 μm-5.6 μm; and / or, K 90 ≤1.3.
[0024] According to some embodiments of this application, the XRD pattern of the positive electrode active material A has characteristic diffraction peaks of the (003) crystal plane, and the 2θ of the characteristic diffraction peaks of the (003) crystal plane is A. 003 The XRD pattern of the positive electrode active material shows characteristic diffraction peaks of the (003) crystal plane, and the 2θ of the characteristic diffraction peaks of the (003) crystal plane is B. 003 , 0.003°≤A 003 -B 003 ≤0.020°.
[0025] According to some embodiments of this application, the positive electrode active material A is crushed and mixed with source M in an air atmosphere, and after introducing fluorine-containing gas, it is left to stand for 3-10 minutes.
[0026] According to some embodiments of this application, the time for the low-temperature plasma reaction is 1 min to 30 min, preferably 5 min to 20 min.
[0027] According to some embodiments of this application, the temperature of the secondary sintering is 300℃-920℃.
[0028] According to some embodiments of this application, the secondary sintering time is 3h-20h.
[0029] According to some embodiments of this application, the heating rate of the secondary sintering is 2℃ / min-10℃ / min.
[0030] According to some embodiments of this application, the volume concentration of oxygen in the atmosphere of the secondary sintering is ≥25%.
[0031] The third aspect of this application provides a positive electrode sheet, including the positive active material provided in the first aspect of this application or the positive active material prepared by the method provided in the second aspect of this application.
[0032] The fourth aspect of this application provides a battery including the positive electrode provided in the third aspect of this application.
[0033] The fifth aspect of this application provides an electrical device, including the battery provided in the fourth aspect of this application. Attached Figure Description
[0034] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which: Figure 1 The EDS diagrams of the positive electrode active materials prepared in Example 3 and Comparative Example 3 of this application are shown.
[0035] Figure 2 The XRD pattern of the positive electrode active material prepared in Example 3 of this application is shown.
[0036] Figure 3 The XRD pattern of the positive electrode active material prepared in Comparative Example 2 of this application is shown. Detailed Implementation
[0037] The embodiments of this application are described in detail below. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0038] A first aspect of this application provides a positive electrode active material, the positive electrode active material comprising an O3-type layered oxide, the positive electrode active material comprising a compound represented by Formula I: Na x (Ni a Fe b Mn c T n Mp )F k O q Formula I, wherein, 0.80≤x≤1.10, 0.30≤a≤0.35, 0.30≤b≤0.35, 0.30≤c≤0.35, 0<n≤0.5, 0<p≤0.05, a+b+c+n+p=1, 0.01≤k≤0.1, k+q=2, T comprises one or more of Cu, Co, V, Mg, Ca, Sn, Zn, Cr, Ti, Al, Zr, Nb, Y, W, La, Li, and M comprises one or more of Zn, Al, Ti, Li, Cu, Co, B, V, Cr, Ca, Mg, Sn, Zr, Nb, Y, W, La; the sodium interlayer spacing of the positive electrode active material is d Na , and the transition metal interlayer spacing is d TMO2 , 3.6500Å<d Na <3.6600Å, 1.7200Å<d TMO2 <1.7225Å.
[0039] By way of example, x may be 0.8, 0.85, 0.9, 0.95, 1, 1.05, 1.1, etc.; a may be 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, etc.; b may be 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, etc.; c may be 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, etc.; n may be 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, etc.; p may be 0.01, 0.02, 0.03, 0.04, 0.05, etc.; k may be 0.01, 0.02, 0.04, 0.06, 0.08, 0.1, etc.; d Na may be 3.6501Å, 3.6505Å, 3.6510Å, 3.6520Å, 3.6530Å, 3.6540Å, 3.6550Å, 3.6560Å, 3.6570Å, 3.6580Å, 3.6590Å, 3.6599Å, etc.; d TMO2 may be 1.7200Å, 1.7203Å, 1.7210Å, 1.7212Å, 1.7215Å, 1.7217Å, 1.7219Å, 1.7220Å, 1.7221Å, 1.7223Å, 1.7225Å, etc.
[0040] In this application, the proposed positive electrode active material is an O3-type layered oxide with 0.80≤x≤1.10, which can improve the battery capacity and control the sodium layer spacing and transition metal layer spacing of the positive electrode active material. The larger sodium layer spacing expands the sodium layer spacing, which can improve the migration rate of sodium ions in the positive electrode active material layer and improve the kinetic performance of the positive electrode active material. The smaller transition metal layer spacing shrinks the transition metal layer spacing, which can ensure the ideal sodium ion diffusion rate of the positive electrode active material and suppress the slippage of the transition metal layer during charging and discharging, thereby improving the battery capacity, rate performance and cycle stability.
[0041] It is understandable that O3-type layered oxides typically have an α-NaFeO2-type structure, belonging to the hexagonal crystal system. In this structure, sodium ions occupy the 3a position, oxygen ions form a hexagonal close-packed structure, while transition metal ions occupy the 3b position, forming an oxygen octahedral structure.
[0042] It is understandable that the chemical formula of the positive electrode active material can be determined by the ICP method: the instrument used is PE Optima7000DV, and the test conditions are that 0.1g of sample is completely dissolved in a mixed acid solution of 3mL HNO3 + 9mL HCl, and then diluted to 250mL for testing.
[0043] The crystal form, sodium interlayer spacing, and transition metal interlayer spacing of the positive electrode active material can be determined by XRD. As an example, the instrument used is an X-ray diffractometer (Rigaku, Smart Lab 9KW). The test conditions are: the X-ray source is Cu Kα rays, the scanning range is 10°-80°, the scanning rate is 1° / min, and the scanning step size is 0.02°.
[0044] According to some specific embodiments of this application, the XRD pattern of the positive electrode active material has a characteristic diffraction peak of the (104) crystal plane at a 2θ of 40°-42.5°, and the full width at half maximum (FWHM) of the characteristic diffraction peak of the (104) crystal plane is W. 104 , 0.179°≤W 104 ≤0.202°. As an example, W 104 The half-width of the characteristic diffraction peaks of the positive electrode active material (104) crystal plane can be 0.179°, 0.180°, 0.185°, 0.190°, 0.195°, 0.200°, 0.202°, etc. By controlling the half-width of the characteristic diffraction peaks of the positive electrode active material (104) crystal plane within the above range, it can be ensured that the grain size meets the requirements and does not affect the capacity, rate, compaction density and other properties of the positive electrode active material; it can also reduce the residual alkali content, thereby improving the capacity, rate and cycle stability of the battery containing it.
[0045] According to some embodiments of the present application, in the XRD pattern of the positive electrode active material, there is a characteristic diffraction peak of the (003) crystal plane, and 2θ of the characteristic diffraction peak of the (003) crystal plane is B 003 , 16.580°≤B 003 ≤16.630°. For example, B 003 can be 16.580°, 16.590°, 16.600°, 16.610°, 16.620°, 16.630°, etc. Controlling the 2θ value B of the characteristic diffraction peak of the (003) crystal plane of the positive electrode active material 003 within the above range indicates that after the F element is doped into the outer crystal lattice, the lattice parameters of the positive electrode active material and the peak position of the characteristic diffraction peak will change, which avoids excessive deintercalation of active sodium inside the positive electrode material, and the surface coating element M, the fluorination modified layer, and the positive electrode active material particles fully interact, so that the rate performance and high-voltage cycle stability performance of the positive electrode active material are effectively improved.
[0046] According to some embodiments of the present application, the unit cell parameters a and c of the positive electrode active material satisfy: 2.9664Å<a<2.9810Å; 16.1200Å<c<16.1450Å. As an example, the unit cell parameter a can be 2.9665, 2.9680, 2.9700, 2.9750, 2.9800, 2.9809, etc., and the unit cell parameter c can be 16.1200, 16.1250, 16.1300, 16.1350, 16.1400, 16.1450, etc. Controlling the two unit cell parameters within the above ranges indicates that the doping element F enters the interior of the crystal lattice of the positive electrode active material, because F - has an ionic radius (1.33 Å) smaller than that of O 2- (1.44 Å), and the F element has strong electronegativity, which changes the binding energy of the O-O bond, thereby compressing the local crystal structure, making the unit cell parameters a and c of the positive electrode active material reach the above ranges, which helps to increase the diffusion rate of sodium ions and maintain structural stability, thereby improving the rate performance and cycle performance of the battery containing the above positive electrode active material.
[0047] It can be understood that the unit cell parameters a and c of the positive electrode active material can be tested by XRD.
[0048] According to some specific embodiments of the present application, 5.4250<c / a<5.4420. For example, c / a may be 5.4251, 5.4300, 5.4350, 5.4400, 5.4419, etc. Therefore, controlling the ratio c / a of the lattice parameters within the above range helps to further increase the diffusion rate of sodium ions, maintain the structural stability of the positive electrode active material, and thereby improve the rate performance and cycle performance of a battery containing the above positive electrode active material.
[0049] According to some embodiments of the present application, the positive electrode active material layer includes a main body and a coating layer formed on at least a partial surface of the main body, and the coating layer includes a metal fluoride. As an example, the metal fluoride of the coating layer may be sodium fluoride, titanium fluoride, etc. Accordingly, the coating layer can isolate the positive electrode active material from contact with the electrolyte, reduce side reactions between the two, and the coating layer has excellent ion-conducting properties, which can further improve the rate performance and cycle performance of a battery containing the above positive electrode active material.
[0050] It can be understood that the coating structure of the positive electrode active material can be observed by a scanning electron microscope and a transmission electron microscope.
[0051] According to some embodiments of the present application, based on the total mass of the positive electrode active material, the mass proportion of element M is ω(M), 0.1%<ω(M)<2%. For example, ω(M) may be 0.11%, 0.2%, 0.3%, 0.5%, 0.7%, 0.9%, 1%, 1.2%, 1.4%, 1.5%, 1.7%, 1.9%, 1.99%, etc. Controlling the mass proportion of element M in the positive electrode active material within the above range results in an appropriate content of the coating element M, which can ensure that the capacity of the positive electrode active material does not decrease, and improve its rate performance and high-voltage cycle stability.
[0052] According to some specific embodiments of the present application, based on the total mass of the positive electrode active material, the mass proportion of fluorine element is ω(F), 0.15×ω(M)<ω(F)<0.70×ω(M). As an example, ω(F) may be 0.16×ω(M), 0.2×ω(M), 0.3×ω(M), 0.4×ω(M), 0.5×ω(M), 0.6×ω(M), 0.7×ω(M), etc. Controlling the relationship between the content of fluorine element and element M within the above range results in appropriate contents of the coating element M and fluorine element, and can reduce the increase in the content of NiO impurity phase caused by excessive fluorine element content, which can ensure that the capacity of the positive electrode active material does not decrease, and improve its rate performance and high-voltage cycle stability.
[0053] In a second aspect, the present application provides a method for preparing the positive electrode active material provided in the first aspect of the present application, and the method comprises: S1. Mix the positive electrode active material precursor, sodium source, and optionally T source, and sinter once to obtain positive electrode active material A.
[0054] This step involves sintering a mixture of the precursor, sodium source, and optionally T source in one step to obtain a positive electrode active material A that does not contain M or F elements.
[0055] According to some embodiments of this application, the sintering temperature is 900~1050℃. For example, it can be 900℃, 950℃, 1000℃, 1050℃, etc.
[0056] According to some specific embodiments of this application, the precursor may be one or more oxides or hydroxides of nickel, iron, and manganese.
[0057] Doping with element T can effectively improve the electrical properties of cathode active materials and meet the requirements of subsequent plasma surface fluorination modification, thereby synergistically improving the surface modification effect of cathode active material particles.
[0058] S2. Crush the positive electrode active material A, mix it with the M source, place it in a low-temperature plasma device, introduce fluorine-containing gas, and carry out a low-temperature plasma reaction to obtain the modified positive electrode active material.
[0059] This step involves a low-temperature plasma reaction, where plasma treatment is performed in a fluorine-containing atmosphere to directly and uniformly load the target element fluorine onto the surface of the positive electrode active material particles. Fluorine-containing plasma (F, F) - CF3 + CF2 2+ CF3 - (etc.) On the one hand, it can react with residual sodium on the surface of positive electrode active material A particles, reducing residual alkali; on the other hand, it can form sodium fluoride in situ with sodium during cycling. Sodium fluoride can act as a protective layer, suppressing side reactions between the electrolyte and the positive electrode active material, and can also enhance the sodium affinity of the positive electrode active material, optimize the sodium ion conductivity on the surface of the positive electrode active material, and improve the kinetic performance of the positive electrode active material.
[0060] Furthermore, some fluorine can be doped into the outer layer of the positive electrode active material particles, forming a gradient structure. This substitutes some oxygen atoms in the layered lattice of the outer layer, enhancing the TO and MO bond forces in the transition metal layer, optimizing the structural stability of the transition metal layer, and suppressing the slippage of the transition metal layer under high voltage. Fluorine doping can also cause the transition metal layer to shrink, thereby increasing the sodium interlayer spacing to some extent and further improving the sodium ion diffusion kinetics of the positive electrode material.
[0061] According to some specific embodiments of this application, the voltage of the low-temperature plasma reaction is 5kV-20kV, for example, it can be 5kV, 7kV, 9kV, 10kV, 12kV, 15kV, 17kV, 19kV, 20kV, etc. Controlling the voltage of the low-temperature plasma reaction within the above range allows fluorine-containing gas to form active fluorine plasma (F, F). - CF3 + CF2 2+ CF3 - Fluorine plasma reacts with residual alkali and M source on the surface of the positive electrode active material to generate a protective layer, which inhibits side reactions between the electrolyte and the positive electrode active material. On the other hand, it can enhance the sodium affinity of the positive electrode active material, optimize the sodium ion conductivity on the surface of the positive electrode active material, and improve the kinetic performance of the positive electrode active material.
[0062] According to some embodiments of this application, the frequency of the low-temperature plasma reaction is 30kHz-70kHz. For example, it can be 30kHz, 35kHz, 40kHz, 45kHz, 50kHz, 55kHz, 60kHz, 65kHz, 70kHz, etc. Controlling the frequency of the low-temperature plasma reaction within the above range allows the fluorine-containing gas to form active fluorine plasma (F, F). - CF3 + CF2 2+ CF3 - Fluorine plasma reacts with residual alkali and M source on the surface of the positive electrode active material to generate a protective layer, which inhibits side reactions between the electrolyte and the positive electrode active material. On the other hand, it can enhance the sodium affinity of the positive electrode active material, optimize the sodium ion conductivity on the surface of the positive electrode active material, and improve the kinetic performance of the positive electrode active material.
[0063] According to some specific embodiments of this application, the flow rate of the fluorine-containing gas is 3 slm-20 slm. For example, it can be 3 slm, 5 slm, 7 slm, 9 slm, 10 slm, 12 slm, 15 slm, 17 slm, 20 slm, etc. Controlling the flow rate of the fluorine-containing gas within the above range can ensure that the fluorine content entering the positive electrode active material is appropriate, and can avoid excessive fluorine content in the positive electrode active material caused by excessive flow rate of fluorine-containing gas. It can also prevent the active sodium inside the lattice of sodium-ion O3 type layered oxide positive electrode active material from being excessively extracted during secondary sintering, prevent excessive shift of the (003) peak position, and ensure that the capacity of the positive electrode active material is not affected. In addition, it can alleviate the Ginger-Taylor effect of excessive fluorine doping in the lattice, which exacerbates the Mn element, and ensure the cycle performance of the positive electrode material.
[0064] According to some embodiments of this application, the fluorine-containing gas includes a mixture of an inert gas and a fluorine-containing organic gas, wherein the volume ratio of the inert gas to the fluorine-containing organic gas is 2.5:7.5-8:2. For example, it can be 2.5:7.5, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2, etc. Controlling the volume ratio of the inert gas to the fluorine-containing organic gas within the above range can avoid insufficient fluorine entering the positive electrode active material, and can prevent excessive fluorine content in the positive electrode active material caused by excessive flow of fluorine-containing gas. It can also prevent excessive extraction of active sodium inside the lattice of sodium-ion O3-type layered oxide positive electrode active material during secondary sintering, prevent excessive shift of the (003) peak position, and ensure the capacity of the positive electrode active material; and can alleviate the exacerbation of the Ginger-Taylor effect of excessive fluorine doping in the lattice, and ensure the cycle performance of the positive electrode material.
[0065] According to some embodiments of this application, the inert gas includes one or more of helium, argon, and nitrogen. These gases are highly stable and will not participate in low-temperature plasma reactions.
[0066] According to some embodiments of this application, the fluorinated organic gas includes one or more of CF4, C4F8, C5F8, and C6F6. The aforementioned fluorinated organic gases can react under certain voltage and frequency to form active fluorine plasma (F, F). - CF3 + CF2 2+ CF3 - Fluorine plasma reacts with residual alkali and M source on the surface of the positive electrode active material to generate a protective layer, which inhibits side reactions between the electrolyte and the positive electrode active material. On the other hand, it can enhance the sodium affinity of the positive electrode active material, optimize the sodium ion conductivity on the surface of the positive electrode active material, and improve the kinetic performance of the positive electrode active material.
[0067] According to some embodiments of this application, after the positive electrode active material A is crushed, the particle size corresponding to 50% of the particle size volume distribution is D. 50 The particle size corresponding to 90% of the volume distribution is D. 90 The particle size corresponding to a volume distribution of 10% is D. 10 K 90 =(D 90 -D 10 ) / D 50 ;D 50 The thickness ranges from 1.5 μm to 8.0 μm. According to other embodiments of this application, D... 50 The thickness is 2.0 μm-6.5 μm, more preferably 4 μm-5.6 μm, for example, D. 50 The diameter can be 1.5μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, etc., and the positive electrode active material A, which does not contain M and F elements, will be used for D.50 Controlling the particle size within the above range is beneficial for obtaining a positive electrode active material with a better particle size range, which can improve the rate performance and cycle performance of the battery.
[0068] According to some embodiments of this application, K 90 ≤1.3. For example, it can be 1.3, 1.2, 1.1, 1, 0.9, 0.8, 0.7, 0.6, 0.5, 0.4, 0.3, 0.2, 0.1, etc. Controlling the particle size uniformity of the positive electrode active material within the above range results in a narrow particle size distribution, which can improve the uniformity of the particle size distribution of the positive electrode active material. This, in turn, determines the XRD peak position and fluorine content of the positive electrode active material in subsequent processing, thereby improving the rate performance and cycle performance of the battery.
[0069] It's understandable, D 50 D 90 D 10 K 90 These parameters can be measured using a laser particle size analyzer, specifically a Malvern particle size analyzer.
[0070] According to some embodiments of this application, the XRD pattern of the positive electrode active material A has characteristic diffraction peaks of the (003) crystal plane, and the 2θ of the characteristic diffraction peaks of the (003) crystal plane is A. 003 The XRD pattern of the positive electrode active material shows characteristic diffraction peaks of the (003) crystal plane, and the 2θ of the characteristic diffraction peaks of the (003) crystal plane is B. 003 , 0.003°≤A 003 -B 003 ≤0.020°. For example, it can be 0.003°, 0.005°, 0.007°, 0.01°, 0.015°, 0.02°, etc., where A... 003 -B 003 The value is controlled within the above range, indicating that after the F element is doped into the outer lattice, the lattice parameters of the positive electrode active material and the peak position of the characteristic diffraction peak will change, avoiding excessive extraction of active sodium inside the positive electrode material. Moreover, the surface coating element M, the fluorinated modification layer, and the particles of the positive electrode active material interact fully, so that the rate performance and high voltage cycle stability of the positive electrode active material are effectively improved.
[0071] According to some embodiments of this application, the positive electrode active material A is crushed and mixed with source M in an air atmosphere. After introducing fluorine-containing gas, it is allowed to stand for 3-10 minutes. For example, the standing time can be 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, etc., to allow the fluorine-containing gas to fill the mixing chamber and exhaust the air.
[0072] According to some embodiments of this application, the sodium source includes one or two of sodium carbonate and sodium hydroxide; the T source and M source include one or more of the corresponding oxides and hydroxides.
[0073] According to some embodiments of this application, the mixing process in step S2 is divided into two stages: first, ordinary mixing is performed in an air atmosphere; then, plasma-assisted mixing is performed by introducing fluorine-containing gas into the mixing tank and then starting the plasma generator. According to some embodiments of this application, the total mixing time is 0.3h to 3h, for example, it can be 0.3h, 0.5h, 1h, 2h, 3h, etc.
[0074] According to some embodiments of this application, the low-temperature plasma reaction time is 1 min to 30 min, preferably 5 min to 20 min. For example, it can be 1 min, 3 min, 5 min, 7 min, 9 min, 10 min, 12 min, 14 min, 15 min, 17 min, 19 min, 20 min, etc. This allows for appropriate content of coating element M and fluorine, and avoids the increase in NiO impurity phase content caused by excessive fluorine content, ensuring that the capacity of the positive electrode active material does not decrease, and improving its rate performance and high-voltage cycling stability.
[0075] S2. The modified positive electrode active material is sintered a second time to obtain the positive electrode active material.
[0076] In this step, the modified positive electrode active material after low-temperature plasma reaction is sintered a second time to allow the coating layer on the surface of the positive electrode active material to fully interact with the substrate, thereby improving the stability of the positive electrode active material and further enhancing the rate performance and cycle performance of the battery.
[0077] According to some embodiments of this application, the secondary sintering temperature is 300℃-920℃. For example, it can be 300℃, 400℃, 500℃, 600℃, 700℃, 800℃, 900℃, 920℃, etc. Controlling the secondary sintering temperature within the above range can, on the one hand, ensure that the coating agent M and fluorine can fully react with the residual sodium on the surface of the positive electrode active material particles, and allow some fluorine to enter the lattice of the outer layer structure of the positive electrode particles, thereby improving the fluorination modification effect on the particle surface; on the other hand, it can prevent excessive extraction of active sodium from the particle lattice, ensuring that the capacity of the positive electrode active material does not decrease while improving the kinetic performance and structural stability during cycling.
[0078] According to some embodiments of this application, the secondary sintering time is 3h-20h, for example, it can be 3h, 5h, 7h, 9h, 10h, 12h, 14h, 15h, 17h, 19h, 20h, etc., thereby enabling the coating agent M and fluorine to fully react with the residual sodium on the surface of the positive electrode active material particles, and allowing some fluorine to enter the lattice of the outer layer structure of the positive electrode particles, improving the fluorination modification effect on the particle surface; it can prevent excessive extraction of active sodium from the particle lattice, ensuring that the capacity of the positive electrode active material does not decrease, while improving the kinetic performance and structural stability during cycling.
[0079] According to some embodiments of this application, the heating rate of the secondary sintering is 2℃ / min-10℃ / min. For example, it can be 2℃ / min, 4℃ / min, 5℃ / min, 7℃ / min, 9℃ / min, 10℃ / min, etc. This allows the coating agent M and fluorine to fully react with the residual sodium on the surface of the positive electrode active material particles, and allows some fluorine to enter the lattice of the outer layer structure of the positive electrode particles, improving the fluorination modification effect on the particle surface; it can prevent excessive extraction of active sodium from the particle lattice, ensuring that the capacity of the positive electrode active material does not decrease while improving kinetic performance and structural stability during cycling.
[0080] According to some embodiments of this application, the volume concentration of oxygen in the secondary sintering atmosphere is ≥25%. For example, it can be 25%, 30%, 40%, 50%, 70%, 90%, 100%, etc. This allows the coating agent M and fluorine to fully react with the residual sodium on the surface of the positive electrode active material particles, and allows some fluorine to enter the lattice of the outer layer structure of the positive electrode particles, improving the fluorination modification effect on the particle surface; it can prevent excessive extraction of active sodium from inside the particle lattice, ensuring that the capacity of the positive electrode active material does not decrease while improving the kinetic performance and structural stability during cycling.
[0081] In summary, the method for preparing the positive electrode active material proposed in this application utilizes a low-temperature plasma surface treatment technology that is relatively inexpensive, has minimal environmental impact, generates highly reactive free radicals, and produces a uniform and robust surface modification layer. This technology is used to modify the surface of sodium-ion battery positive electrode active materials. The positive electrode active material A, sintered once, undergoes plasma-assisted coating and mixing in a fluorine-containing gas atmosphere. A second sintering process then forms a uniform fluorinated modification layer on the surface of the coated positive electrode active material A particles, ultimately yielding a surface-modified positive electrode active material. During the synthesis process, by controlling the process and limiting the peak position shift of the second sintering material, the lattice parameters of the positive electrode active material obtained from the second sintering satisfy a certain relationship. This allows the second-sintered positive electrode active material to possess better rate performance and cycle performance without affecting capacity and air stability.
[0082] The third aspect of this application provides a positive electrode sheet, including the positive active material provided in the first aspect of this application or the positive active material prepared by the method provided in the second aspect of this application.
[0083] According to an embodiment of the present invention, the positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector. The positive active material layer includes the aforementioned positive active material. The positive current collector can be a metal foil or a composite current collector (a metal material can be disposed on a polymer substrate to form a composite current collector). For example, the positive current collector can be an aluminum foil.
[0084] According to some embodiments of the present invention, the positive electrode active material layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, or fluorinated acrylate resin.
[0085] According to some embodiments of the present invention, the positive electrode active material layer may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.
[0086] According to some embodiments of the present invention, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto a positive current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0087] It should be noted that the features and advantages described above for the positive electrode active material and its preparation method also apply to this positive electrode sheet, and will not be repeated here.
[0088] In a fourth aspect, the present invention provides a battery. According to an embodiment of the invention, the battery includes at least one of the positive electrode plates described in the third aspect.
[0089] As an example, a battery includes a positive electrode, a negative electrode, an electrolyte, and a separator, with the separator located between the positive and negative electrodes. During charging and discharging, active ions move back and forth between the positive and negative electrodes, inserting and releasing. The electrolyte acts as a conductor of ions between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits between the positive and negative electrodes while allowing ions to pass through.
[0090] According to an embodiment of the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material. The negative electrode current collector can be a metal foil or a composite current collector (a metal material can be disposed on a polymer substrate to form a composite current collector). For example, the positive electrode current collector can be a copper foil.
[0091] According to some embodiments of the present invention, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and sodium titanate, etc.
[0092] According to some embodiments of the present invention, the negative electrode active material layer may optionally include a conductive agent. The conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.
[0093] According to some embodiments of the present invention, the negative electrode active material layer may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0094] According to some embodiments of the present invention, the negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet, such as negative electrode active material, conductive agent, and binder, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto a negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing, and other processes.
[0095] According to some embodiments of the present invention, the negative electrode sheet may include a sodium sheet or a sodium alloy, such as a sodium-indium alloy.
[0096] According to further embodiments of the present invention, the type of separator is not particularly limited, and any known porous separator with good chemical and mechanical stability can be selected. As an example, the material of the separator may include at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, or polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0097] According to further embodiments of the present invention, there is no specific limitation on the type of electrolyte, which can be selected according to requirements. For example, the electrolyte can be in a gel state or a completely solid state. According to some specific embodiments of the present invention, the electrolyte is an electrolyte solution comprising a sodium salt and a solvent.
[0098] According to some specific embodiments of the present invention, the sodium salt may include at least one of sodium hexafluorophosphate, sodium difluorooxalate borate, sodium tetrafluoroborate, sodium dioxalate borate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethanesulfonate, or sodium bis(trifluoromethanesulfonyl)imide.
[0099] According to some specific embodiments of the present invention, the solvent may include at least one selected from ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, ethylene glycol dimethyl ether, methyl ethyl sulfone, or diethyl sulfone.
[0100] In some embodiments of this application, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0101] It should be noted that the features and advantages described above for the positive electrode also apply to this solid-state battery, and will not be repeated here.
[0102] In a fifth aspect, the present invention provides an electrical device. According to an embodiment of the invention, the electrical device includes the battery described above. According to an embodiment of the invention, the electrical device may include, but is not limited to, mobile phones, laptops, electric vehicles, etc.
[0103] It should be noted that the features and advantages described above for the battery also apply to this electrical device, and will not be repeated here.
[0104] The present invention will now be described with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the invention in any way. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in the art or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0105] In the following examples, all raw materials are commercially available unless otherwise specified.
[0106] Example 1 Step 1: According to the stoichiometric ratio, add the sodium-ionized oxygen precursor (chemical formula Ni) 1 / 3 Fe 1 / 3 Mn 1 / 3(OH)2) was mixed with Na2CO3 and Ti(OH)4 in a certain mass ratio and then sintered once. The amount of sodium source used (i.e., n(Na) / n(Me), Me=Ni+Fe+Mn+T+M) is shown in Table 1. The first sintering was carried out in an atmosphere with an oxygen concentration of 50 vol%, and the temperature was raised to 950℃ at a heating rate of 3.0℃ / min, held at 950℃ for 16 h, and then cooled down with the furnace. Step 2: After the positive electrode active material A obtained by sintering in Step 1 is cooled, it is crushed by air jet mill. The median particle size D50 and particle size distribution K90 of the crushed positive electrode active material A are shown in Table 1. XRD analysis is performed on it, and its (003) peak 2θ is shown in Table 2. Step 3: The crushed positive electrode active material A from Step 2 and the coating agent CuO (M source) are added to a dielectric barrier low-temperature plasma-assisted mixer in a certain proportion. The mass percentage of element M in the positive electrode active material is shown in Table 2. The first stage of ordinary mixing is carried out first, with air as the mixing atmosphere and a mixing time of 60 minutes. Step 4: After the ordinary mixing process described in Step 3 is completed, a mixture of helium and fluorocarbon gas with a volume ratio of 7:3 and the fluorocarbon gas being C6F6 is introduced into the mixing chamber of the plasma-assisted mixer through the gas inlet. After 5-10 minutes of gas introduction, the mixer and plasma generator are started to carry out the second stage of plasma-assisted mixing. The plasma reactor voltage is adjusted to 8kV, the frequency to 40Hz, the airflow speed is adjusted to 8slm, and the mixing time is 10 minutes to obtain the positive electrode material A after surface coating and fluorination modification. The surface fluorine content is shown in Table 2. Step 5: The surface-fluorinated modified cathode material A described in Step 4 is subjected to secondary sintering. The heating rate v1 is 3℃ / min, the target temperature T is 700℃, and the temperature is held for 10h. Then, the material is cooled down with the furnace and crushed to obtain the surface-fluorinated modified sodium cathode active material. After that, XRD analysis and electrical performance testing are performed on it. The (003) peak position is shown in Table 2, the lattice parameters are shown in Table 2, and the electrical performance data are shown in Table 3.
[0107] The preparation methods of the positive electrode active materials in the other embodiments and comparative examples are the same as in Example 1, with the differences detailed below, see Table 1.
[0108] Compared to Example 1, in Example 2, the n(Na) / n(Me) ratio and the doping elements are different in step one, resulting in positive electrode active materials A with different compositions; In step four, the volume ratio of nitrogen to fluorocarbon gas is 6.0:4.0, the fluorocarbon gas is C4F8, the plasma reactor voltage is 12kV, the frequency is 50Hz, the gas flow rate is adjusted to 10slm, and the mixing time is 12min, to obtain the coated and surface-fluorinated modified positive electrode active material.
[0109] Compared to Example 2, in Example 3, the n(Na) / n(Me) ratio is different in step one, resulting in positive electrode active materials with different compositions; In step four, the volume ratio of nitrogen to fluorocarbon gas is 5.0:5.0, the fluorocarbon gas is C4F8, the plasma reactor voltage is 12kV, the frequency is 55Hz, the gas flow rate is adjusted to 12slm, and the mixing time is 14min, thus obtaining a positive electrode active material that has been coated and surface-fluorinated.
[0110] Compared to Example 3, the coating agent used in step three of Example 4 is TiO2. 2, .
[0111] Compared to Example 3, the median particle size D of the crushed positive electrode active material A in step three of Example 5 is different. 50 Changes occur, particle size distribution K 90 Things have changed.
[0112] Compared to Example 3, in step four of Example 6, the volume ratio of inert gas to fluorinated organic gas and the flow rate of fluorinated gas change.
[0113] Compared to Example 3, in step four of Example 7, the volume ratio of inert gas to fluorinated organic gas and the flow rate of fluorinated gas change.
[0114] Compared to Example 3, in step four of Example 8, the volume ratio of inert gas to fluorinated organic gas and the flow rate of fluorinated gas change.
[0115] Compared to Example 3, the low-temperature plasma reaction voltage changes in step four of Example 9.
[0116] Compared to Example 3, the low-temperature plasma reaction voltage changes in step four of Example 10.
[0117] Compared to Example 3, the low-temperature plasma reaction voltage changes in step four of Example 11.
[0118] Compared to Example 3, the low-temperature plasma reaction frequency changes in step four of Example 12.
[0119] Compared to Example 3, the low-temperature plasma reaction frequency changes in step four of Example 13.
[0120] Compared to Example 3, in step one of Example 14, the composition of the sodium-ion precursor is different, and the n(Na) / n(Me) ratio is different, resulting in positive electrode active materials with different compositions.
[0121] Compared to Example 3, the sodium-ion precursor composition is different in step one of Example 15, resulting in positive electrode active materials with different compositions.
[0122] Compared to Example 3, in step one of Example 16, the sodium-ion precursor composition is different, resulting in positive electrode active materials with different compositions.
[0123] Compared to Example 1, Comparative Example 1 only underwent the ordinary mixing described in step three for 75 minutes, without the plasma-assisted mixing described in step four. Then, a second sintering was performed according to step five.
[0124] Compared to Example 3, in step four of Comparative Example 2, the volume ratio of nitrogen to fluorocarbon gas was 1.0:9.0, the fluorocarbon gas was CF4, the plasma reactor voltage was 22kV, the frequency was 75Hz, the gas flow rate was adjusted to 22slm, and the plasma-assisted mixing time was 30min, thus obtaining a positive electrode active material that had been coated and surface-fluorinated.
[0125] Compared to Example 3, the coating agent used in Step 3 of Comparative Example 3 was CuF2, and the CuF2 content is shown in Table 2; furthermore, only the ordinary mixing described in Step 3 was performed, with a mixing time of 75 minutes, without the plasma-assisted mixing described in Step 4. Then, a second sintering was performed according to Step 5.
[0126] Compared to Example 3, in step four of Comparative Example 4, the volume ratio of inert gas to fluorinated organic gas and the flow rate of fluorinated gas changed.
[0127] Table 1
[0128] Performance testing 1. Morphology Test: EDS surface scanning tests were performed on the positive electrode active materials prepared in Example 3 and Comparative Example 3 to determine the distribution of F element on the surface of the positive electrode active materials. It was found that, with the coating agent content and F content being basically the same, Example 3, through plasma-assisted mixing, could further expand the sodium interlayer spacing and reduce the transition metal interlayer spacing, thereby stabilizing the crystal structure and improving capacity, cycle life, and other isoelectric properties. This indicates that plasma-assisted mixing plays a crucial role in improving the electrochemical performance of the positive electrode material. The EDS values corresponding to the F element in the positive electrode active materials of Comparative Example 3 and Example 3 are as follows: Figure 1 As shown in the above EDS diagram for element F, it can be seen that in Example 3, plasma-assisted mixing can effectively improve the uniformity of element F distribution, thereby constructing a more uniform and stable surface coating layer and improving electrical properties such as capacity, rate capability, and cycle life.
[0129] 2. XRD test: The positive electrode active materials prepared in the examples and comparative examples were tested using an X-ray diffractometer (Rigaku, Smart Lab 9KW). The test conditions were: the X-ray source was Cu Kα rays, the scanning range was 10°-80°, the scanning rate was 1° / min, and the scanning step size was 0.02°. The XRD patterns were obtained.
[0130] The XRD patterns of the positive electrode active materials of Example 3 and Comparative Example 2 are shown below. Figure 2 and 3 As shown, by Figure 2 and Figure 3 It can be seen that Example 3 has no impurity phase under the condition of appropriate F content, while Comparative Example 2 shows a NiO impurity peak at 2θ of 43.2° when the F content is too high. Figure 3 (The peak within the red box).
[0131] Sodium interlayer spacing is d Na The spacing between the transition metal layers is d. TMO2 test: d TMO2 =(a / 3-Zzox*c)×2; where the coefficient Zzox is obtained by refining the full spectrum fitting of the sample XRD spectrum using SmartLab Studio II software.
[0132] d Na =a / 3-d TMO2 .
[0133] (104) Full width at half maximum (FWHM) of the characteristic diffraction peaks of the crystal plane 104 Testing: After XRD testing using a SmartLab X-ray diffractometer, W was obtained by full-spectrum fitting using SmartLab Studio II software. 104 .
[0134] (003) The 2θ value A of the characteristic diffraction peak of the crystal plane 003 and B 003 Test: A was obtained after XRD testing using a SmartLab X-ray diffractometer. 003 and B 003 .
[0135] Unit cell parameters a and c were tested: After XRD was performed using a SmartLab X-ray diffractometer, the unit cell parameters a and c were obtained by full-spectrum fitting using SmartLab Studio II software.
[0136] 3. Based on the total mass of the positive electrode active material, the mass ratio of M and F elements was tested: the M element was obtained by inductively coupled plasma (ICP) testing, and the F element was obtained by X-ray fluorescence spectrometry (XRF) testing.
[0137] 4. NiO Content Test: After XRD analysis using a SmartLab X-ray diffractometer, full-spectrum fitting was performed using SmartLab Studio II software. The peak intensities of the NiO impurity phase characteristic peaks and the sodium layer oxygen characteristic peaks were calculated by comparison. The test results are shown in Table 2.
[0138] Table 2
[0139] The specific preparation process of sodium-ion batteries is as follows: Electrode preparation: The sodium-ion battery positive electrode active material, conductive agent SuperP and polyvinylidene fluoride (PVDF) of the above examples and comparative examples are thoroughly mixed with an appropriate amount of N-methylpyrrolidone (NMP) at a mass ratio of 95:3:2 to form a uniform slurry. The slurry is coated on aluminum foil and dried at 120°C for 12 h. Then, it is stamped and formed with a pressure of 100 MPa to produce a positive electrode sheet with a diameter of 12 mm and a thickness of 120 μm.
[0140] Battery Assembly: In an argon-filled glove box with both water and oxygen content less than 5 ppm, the positive electrode, separator, negative electrode, and electrolyte were assembled into a coin-type sodium-ion battery and then allowed to stand for 6 hours. The negative electrode used a 14 mm diameter, 1 mm thick metallic sodium sheet; the separator used a 25 μm thick coated separator; and the electrolyte was a 4:6 mixture of 1 mol / L NaPF6, ethyl methyl carbonate (EMC), and propylene carbonate (PC).
[0141] Electrochemical performance testing: In the following examples and comparative examples, the Shenzhen Xinwei Battery Testing System (CT3008) was used to test the electrochemical performance of R2025 coin cell sodium-ion batteries. The initial charge-discharge capacity test conditions were 0.1C@2-4.0V, 25℃, with a constant voltage cutoff current of 0.02C; the cycle performance test conditions were 1.0C@2-4.0V, 25℃. The coin cell sodium-ion batteries were subjected to constant current charge-discharge tests at 0.1C and 1C to evaluate the discharge specific capacity, rate performance, and cycle performance of the sodium-ion battery cathode material. A higher capacity retention rate during cycling indicates higher material stability and better cycle performance of the battery system.
[0142] The test results of the batteries in the examples and comparative examples are shown in Table 3.
[0143] Table 3
[0144] As can be seen from Tables 1-3, in Examples 1-16 of this application, the sodium layer spacing is large, which is expanded, while the transition metal layer spacing is small, which is contracted. This can ensure the ideal sodium ion diffusion rate of the positive electrode active material, while suppressing the slippage of the transition metal layer during charging and discharging, thereby improving the battery's capacity, rate performance, and cycle stability.
[0145] Compared to Examples 1-16, the positive electrode active material in Comparative Example 1 does not contain fluorine, and the plasma-assisted mixing described in step four is not performed during its preparation. Therefore, no fluorine-containing coating layer forms on the surface of the positive electrode active material, and excessive extraction of active sodium occurs inside the material. This reduces the sodium interlayer spacing and transition metal interlayer spacing, significantly decreasing the battery's capacity, rate performance, and cycle performance. In Comparative Example 2, the sodium interlayer spacing and transition metal interlayer spacing are too high, resulting in an excessively high impurity phase content and a significant reduction in battery capacity. In Comparative Example 3, ordinary mixing is used during the preparation of the positive electrode active material, without the plasma-assisted mixing described in step four. Fluorine cannot form a gradient structure on the outer layer of the positive electrode active material particles, reducing the sodium interlayer spacing and transition metal interlayer spacing, and significantly decreasing the battery's capacity and rate performance. In Comparative Example 4, the sodium interlayer spacing and transition metal interlayer spacing are too low, hindering sodium ion transport and significantly reducing the battery's capacity and rate performance.
[0146] Compared to Example 3, in Example 5, the D of the positive electrode active material A... 90 and K 90 If the value is too large, the D of the obtained positive electrode active material will be affected. 90The increased concentration of fluorine-containing gas in Example 7, compared to Example 3, resulted in a lower battery capacity and slightly poorer rate performance. In Example 7, less fluorine-containing gas was used during the preparation of the positive electrode active material, leading to a lower fluorine content, reduced sodium interlayer spacing, and decreased transition metal interlayer spacing. This resulted in lower stability of the positive electrode active material and reduced battery capacity, rate performance, and cycle performance. In Example 8, compared to Example 3, more fluorine-containing gas was used during the preparation of the positive electrode active material, resulting in an increased fluorine content, increased sodium interlayer spacing, and increased transition metal interlayer spacing. The higher NiO impurity phase content further reduced battery capacity. In Example 10, compared to Example 3, the increased voltage of the low-temperature plasma reaction made it easier for the fluorine-containing plasma to undergo side reactions with the positive electrode active material A. The higher NiO impurity phase content also contributed to a decrease in battery capacity. Compared to Example 3, in Example 11, the voltage of the low-temperature plasma reaction was lower during the preparation of the positive electrode active material. This resulted in insufficient reaction between the fluorine-containing plasma and the positive electrode active material A, leading to a decrease in fluorine content, sodium interlayer spacing, and transition metal interlayer spacing. Consequently, the stability of the positive electrode active material decreased, and the battery's capacity, rate performance, and cycle performance were reduced. Compared to Example 3, the frequency of the low-temperature plasma reaction in Example 13 was too low, resulting in insufficient reaction between the fluorine-containing plasma and the positive electrode active material A. This also led to a decrease in fluorine content, sodium interlayer spacing, and transition metal interlayer spacing, further reducing the stability of the positive electrode active material and consequently, the battery's capacity, rate performance, and cycle performance.
[0147] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0148] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.
Claims
1. A positive electrode active material, characterized in that, The positive electrode active material includes an O3-type layered oxide, and the chemical formula of the positive electrode active material is: Na x (Ni a Fe b Mn c T n M p )F k O q Formula I, wherein 0.80≤x≤1.10, 0.30≤a≤0.35, 0.30≤b≤0.35, 0.30≤c≤0.35, 0<n≤0.5, 0<p≤0.05, a+b+c+n+p=1, 0.01≤k≤0.1, k+q=2, T includes one or more of Cu, Co, V, Mg, Ca, Sn, Zn, Cr, Ti, Al, Zr, Nb, Y, W, La, Li, and M includes one or more of Zn, Al, Ti, Li, Cu, Co, B, V, Cr, Ca, Mg, Sn, Zr, Nb, Y, W, La; The positive electrode active material comprises a main body and a coating layer formed on at least part of the surface of the main body, and the coating layer comprises a metal fluoride; The sodium layer spacing of the positive electrode active material is d. Na The spacing between the transition metal layers is d. TMO2 3.6500Å <d Na <3.6600Å, 1.7200Å <d TMO2 <1.7225Å; The XRD pattern of the positive electrode active material shows characteristic diffraction peaks of the (003) crystal plane, and the 2θ of the characteristic diffraction peaks of the (003) crystal plane is B. 003 16.580°≤B 003 ≤16.630°; The unit cell parameters a and c of the positive electrode active material satisfy: 5.4250<c / a<5.4420.
2. The positive electrode active material according to claim 1, characterized in that, In the XRD pattern of the positive electrode active material, there is a characteristic diffraction peak of the (104) crystal plane at 2θ of 40°-42.5°, and the full width at half maximum (FWHM) of the characteristic diffraction peak of the (104) crystal plane is W. 104 , 0.179°≤W 104 ≤0.202°.
3. The positive electrode active material according to claim 2, characterized in that, The unit cell parameters a and c of the positive electrode active material satisfy: 2.9664Å<a<2.9810Å; 16.1200Å<c<16.1450Å。 4. The positive electrode active material according to claim 3, characterized in that, Based on the total mass of the positive electrode active material, the mass proportion of the M element is ω(M), and 0.1%<ω(M)<2%.
5. The positive electrode active material according to claim 4, characterized in that, Based on the total mass of the positive electrode active material, the mass proportion of the fluorine element is ω(F), and 0.15×ω(M)<ω(F)<0.70×ω(M).
6. A method for preparing the positive electrode active material according to any one of claims 1-5, characterized in that, comprising: mixing a positive electrode active material precursor, a sodium source and a T source, and performing primary sintering to obtain a positive electrode active material A; crushing the positive electrode active material A, mixing the crushed product with an M source, placing the mixture in a low-temperature plasma apparatus, introducing a fluorine-containing gas, and carrying out a low-temperature plasma reaction to obtain a modified positive electrode active material; subjecting the modified positive electrode active material to secondary sintering to obtain the positive electrode active material; wherein the voltage of the low-temperature plasma reaction is 5kV-20kV; the frequency of the low-temperature plasma reaction is 30kHz-70kHz; the flow rate of the fluorine-containing gas is 3slm-20slm; the fluorine-containing gas comprises a mixture of an inert gas and a fluorine-containing organic gas, and the volume ratio of the inert gas to the fluorine-containing organic gas is 2.5:7.5-8:2; the temperature of the primary sintering is 900°C to 1050°C, and the temperature of the secondary sintering is 300°C-920°C.
7. The method according to claim 6, characterized in that, the inert gas comprises one or more of helium, argon and nitrogen; and / or, the fluorine-containing organic gas comprises one or more of CF4, C4F8, C5F8 and C6F6.
8. The method according to claim 7, characterized in that, After the positive electrode active material A is crushed, the particle size corresponding to 50% of the particle size volume distribution is D. 50 The particle size corresponding to 90% of the volume distribution is D. 90 The particle size corresponding to a volume distribution of 10% is D. 10 K 90 =(D 90 -D 10 ) / D 50 ; Among them, D 50 The range is 1.5μm-8.0μm; and / or, K 90 ≤1.3; and / or, The XRD pattern of the positive electrode active material A shows characteristic diffraction peaks of the (003) crystal plane, and the 2θ of the characteristic diffraction peaks of the (003) crystal plane is A. 003 The XRD pattern of the positive electrode active material shows characteristic diffraction peaks of the (003) crystal plane, and the 2θ of the characteristic diffraction peaks of the (003) crystal plane is B. 003 , 0.003°≤A 003 -B 003 ≤0.020°.
9. The method according to claim 8, characterized in that, D 50 The range is 2.0μm-6.5μm.
10. The method according to claim 9, characterized in that, D 50 The range is 4μm-5.6μm.
11. The method according to claim 6, characterized in that, the step of crushing the positive electrode active material A and mixing the crushed product with the M source is carried out in an air atmosphere, and after introducing the fluorine-containing gas, the mixture is left to stand for 3min-10min; and / or, the time of the low-temperature plasma reaction is 1min-30min.
12. The method according to claim 11, characterized in that, The time of the low-temperature plasma reaction is 5min-20min.
13. The method according to claim 6, characterized in that, the time of the secondary sintering is 3h-20h; and / or, the heating rate of the secondary sintering is 2°C / min-10°C / min; and / or, The volume concentration of oxygen in the atmosphere during the secondary sintering is ≥25%.
14. A positive electrode plate, characterized in that, The positive electrode active material includes any one of claims 1-5 or any one of claims 6-13 prepared by the method thereof.
15. A battery, characterized in that, Includes the positive electrode sheet as described in claim 14.
16. An electrical appliance, characterized in that, Includes the battery as described in claim 15.
Citation Information
Patent Citations
Low-residual-alkali-content layered oxide positive electrode material for sodium-ion battery and preparation method of low-residual-alkali-content layered oxide positive electrode material
CN118398796A
